Collagen Content in Skin and Internal Organs of the Tight Skin Mouse: An Animal Model of Scleroderma. (24th October 2013) - Manne, Jayanthi; Markova, Marina; Siracusa, Linda D.; Jimenez, Sergio A.
Abstract : The Tight Skin mouse is a genetically induced animal model of tissue fibrosis caused by a large in-frame mutation in the gene encoding fibrillin-1 (Fbn-1). We examined the influence of gender on the collagen content of tissues in C57BL/6J wild type (+/+) and mutant Tight Skin ( Tsk /+) mice employing hydroxyproline assays. Tissue sections were stained with Masson's trichrome to identify collagen in situ . Adult Tsk /+ mice skin contains ~15% more collagen, on average, than skin from +/+ mice of the same gender. The heart of Tsk /+ males had significantly more collagen than that of +/+ males. No significant gender differences were found in lungs and kidney collagen content. Overall, the collagen content of Tsk /+ males and +/+ males was higher than that of their Tsk /+ and +/+ female counterparts, respectively. Our data confirm increased deposition of collagen in skin and hearts of Tsk /+ mice; however, the effects of the Tsk mutation on collagen content are both tissue specific and gender specific. These results indicate that comparative studies of collagen content between normal and Tsk /+ mice skin and internal organs must take into account gender differences caused by expression of the androgen receptor.